Design and optimization of textures on the surface of crankpin bearing to improve lubrication efficiency and friction power loss of engine. (June 2021) - Wu, Zhenpeng; Nguyen, Vanliem; Le, Vanquynh; Le, Xuanlong; Bui, Vancuong
The study proposes a design and optimization of textures on the surface of crankpin bearing to improve the lubrication efficiency and friction power loss (LE-FPL). A hydrodynamic lubrication model of crankpin bearing considering the impact of the external dynamic load and micro asperity contact is established. Based on the established model, the lubrication textures designed on the bearing surface are then simulated and optimized through the algorithms developed in Matlab environment and multi-objective optimization method. Increasing the oil film pressure and reducing the contact force ( W ac ) in the asperity contact region, friction force ( F f ), and friction coefficient ( µ ) of crankpin bearing are the objective functions to evaluate the LE-FPL. The study results indicate that the lubrication textures designed on the bearing surface have an obvious effect on improving the LE-FPL. Especially, with the optimized textures, the maximum oil film pressure is greatly increased by 44.8% while the maximum values of W ac and F f are significantly reduced by 22% and 25%. Consequently, the lubrication textures added on the surface of crankpin bearing can greatly improve the LE-FPL.